Hubungan Pengetahuan Masyarakat dengan Pemanfaatan Tanaman Obat Keluarga (Toga) di Wilayah Banjarmasin Barat - Indriyani Soraya (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Indonesia has many medicinal plants in various regions. TOGA is used as a means of maintaining health and traditional self-medication which is planted in the yard of the house. According to Riskesdas 2018, the use of TOGA in Indonesia is 24.6%, this is quite low so knowledge is needed with the use of TOGA for the community, especially in RT.24 Kuin Selatan, so that the use of TOGA can be used widely, precisely and beneficially for people's daily lives. The purpose of this study was to determine the relationship between public knowledge and the use of TOGA. Data were collected through a questionnaire. The method using analytical observational with Cross Sectional. Sampling technique using purvosive sampling. The population of the research community RT. 24 Kelurahan Kuin Selatan 187 respondents. The sample of the study was 127 respondents. Data obtained from questionnaires that were distributed to the public and analyzed by Spearman Rank test. The results showed that the majority of people's TOGA knowledge in the good category was 99 respondents (78%), and the use of TOGA in the good category was 121 respondents (95%). Knowledge variable has a relationship with utilization with a significance of 0.003 (<0.05), there is a strength category of low relationship of 0.264 with positive unidirectional results.